(untitled) (INNOVATIVE ECONOMY, 2024)
Ivashchuk O.V., Kazmerchuk V.V. GEOPOLITICAL CONFRONTATION OF COUNTRIES AND ECONOMIC DIMENSIONS OF THE FORMATION OF THE NEW WORLD ORDER Purpose. The purpose of the article is to identify the impact of geopolitical transformations on the development of international economic relations and to determine the economic dimension of the formation of a new world order. Methodology of research. The following general scientific and special methods were used in the course of the study: induction and deduction – at the stage of collecting, systematizing and processing information to identify trends and cause-and-effect relationships in the geopolitical confrontation of countries, as well as to predict possible scenarios for the development of international events; analysis and synthesis – to identify the main trends in the formation of a new world order; abstract and logical – to summarize information from various sources and create a comprehensive view of the problem under study, formulate theoretical conclusions and generalizations; comparative method – to analyse the main vectors of geopolitical confrontation between countries in order to identify specific features, global patterns and cause-and-effect relationships between them; graphic method – to visualize the results of the study. Findings. The multifaceted nature of the process of forming a new world order is substantiated. It has been confirmed that the world order is undergoing changes under the influence of global factors, among which the role of economic factors is increasing. The role of civilizational factors in the formation of geopolitical strategies is revealed. Huntington’s theory of civilizations is analysed. The differences of spatial and civilizational approaches to countries are determined. The basic provisions of the basic theories of geopolitics are disclosed. It has been confirmed that in the post-war period the formation of a global institutional system took place, and global institutions were formed. The role of economic institutions in consolidating the efforts of countries in that period is clarified. The role of the Marshall Plan in helping countries is argued. The specifics of the geopolitical confrontation between the countries, which especially intensified during the Cold War period, are clarified. The current state of geopolitical instability and the main geopolitical risks, including economic ones, are analysed. It is substantiated that geopolitical tension is accompanied by economic and financial fragmentation. Originality. The theoretical aspects of the formation of a new world order under the influence of the geopolitical confrontation of countries and economic transformations gained further development. Practical value. The conducted conclusions, recommendations and results can be used in further scientific studies of the economic determinants of the formation of the new world order and the development of proposals for the integration of countries into the new global economic system. Key words: geopolitics, geopolitical confrontation, geopolitical risks, economic fragmentation, economic transformations, new world order.